The game: creative mediation action. the culture of peace in the classroom (Revista Electrónica REDINE, 2021)
The game is a representation, on many occasions, of who we are. It not only transmits values, but also social and cultural roots of those who practice it. Part of an anthropological vision, of the various playful actions that take place in it. It is important that its promoters: educator, counselor, mediator, discover the human capacities of those who interact by playing. For this reason, the present intervention proposal aims to incorporate the Game as a Creative Action to the teaching practice, who, in their role, is trained as a mediator of processes, applies skills and abilities, with innovative material, for the prevention and resolution of conflicts, improving the coexistence of all the actors of the educational fact, promoting a Culture of Peace. The Creative Strategy In-network-ados is proposed, a game methodology to carry out and turn it into a foundation of knowledge construction processes through training. Theories that support the proposal: De la Torre. (2006), from Creativity, talks about the integration of the game as an educational and formative process, under the pedagogical perspectives applicable to recreational activities. Another element is the Comprehensive Approach to Decision Making proposed by Álvarez, (2004), widely applied in Educational Guidance where situations are generated that promote results that promote the Culture of Peace through Play, to create and agree on rules of coexistence, development of negotiation skills for any circumstance. Constitutive elements are addressed for their applicability, in an environment that promotes the principle of possibility and the principle of freedom.
Keywords: Game; Creativity; Mediation; Education; Culture of Peace